Teaching `out of field' in STEM subjects in Australia: Evidence from PISA 2015 - Chandra Shah; Paul Richardson; Helen Watt (Global Labor Organization (GLO), 2020)
Science, technology, engineering and mathematics (STEM) education is a critical part of a modern education system. Motivating students to learn STEM subjects is however a challenge. Teachers have a critical role in motivating students but to do this effectively they need to have appropriate subject matter knowledge. Data from PISA 2015 show a substantial proportion of teachers in Australian schools are teaching STEM subjects `out-of-field', which is that they do not have the qualifications to teach these subjects. This paper examines the effects of individual teacher characteristics and school context on of out-of-field teaching in STEM subjects. In particular, it examines the role of school autonomy and staff shortage in this. The results show these two variables have a strong association with out-of-field teaching, however, other factors either mediate or confound their effects. A full understanding of the results requires knowing the role of school funding and school budgets in out-of-field teaching. While we do not have direct measures of these in the data, we can infer their likely roles through the effects of other factors, such as school sector and education level of parents of students in the school, in the model.
Keywords: C25; I22; I24; J23; J24; 330; out-of-field teaching; teacher supply and demand; multi-level logit model